Specific Language Impairment and Autism Spectrum Disorder: similarities and differences in narrative discourse - Acosta Rodríguez, Víctor Manuel; Ramírez Santana, Gustavo Mario; Cruz, Atteneri Delgado; Del Valle Hernández, Yermina Nayarit (Revista de Investigación en Logopedia, 2022)
Storytelling is a complex skill that involves linguistic, social, and cognitive skills. The objective of this work is to carry out a comparative analysis of the narrative in children with Autism Spectrum Disorder and Specific Language Impairment, since it is usually compromised. Twenty Autism Spectrum Disorder children, twenty Specific Language Impairment children and a control group of twenty typically developing children participated in this research. For the narrative analysis, the task used was the story Frog, where are you? The production of cohesive resources is lower in the Autism Spectrum Disorder group. On the other hand, errors of omission and grammatical substitutions are more frequent in the Specific Language Impairment group. Intervention must be different for the two groups, with the priority being to improve cohesive and global coherence resources in Autism Spectrum Disorder and to work on functional grammatical errors in Specific Language Impairment.
Keywords: Autism spectrum disorder; Specific language impairment; Narrative; Cohesion; Grammar